2013
DOI: 10.1590/s0100-54052013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da resistência de variedades de Citrus spp. à Xanthomonas citri subsp. citri na região Noroeste Paranaense, em condições de campo

Abstract: A identificação de cultivares com determinados níveis de resistência ao cancro cítrico, com características agronômicas e comerciais desejáveis, assume grande importância para o manejo desta doença. A avaliação de genótipos promissores pode ser fetuada em condições controladas ou em campo. O trabalho teve como objetivo avaliar genótipos de laranja doce (Citrus sinensis), tangerinas (Citrus reticulata) e híbridos quanto à resistência ao cancro cítrico, em diferentes épocas de avaliação. O experimento foi conduz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Washington Navel was ranked as highly susceptible, and it also had the largest lesions, compared with the other varieties. Other field experiment-based observations of ACC severity indicated that the relative susceptibilities of these 9 varieties are similar to our findings (except for Valencia Mutação as its lesions were larger than those of Pera IAC) (30). Thus, using needle-wound inoculation of detached leaves to evaluate resistance to ACC can result in relative varietal disease severities similar to those observed for plants inoculated by spraying and grown under greenhouse conditions, as well as naturally infected plants grown in the field.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Washington Navel was ranked as highly susceptible, and it also had the largest lesions, compared with the other varieties. Other field experiment-based observations of ACC severity indicated that the relative susceptibilities of these 9 varieties are similar to our findings (except for Valencia Mutação as its lesions were larger than those of Pera IAC) (30). Thus, using needle-wound inoculation of detached leaves to evaluate resistance to ACC can result in relative varietal disease severities similar to those observed for plants inoculated by spraying and grown under greenhouse conditions, as well as naturally infected plants grown in the field.…”
Section: Discussionsupporting
confidence: 88%
“…Integrated management of citrus canker includes breeding for resistance, as well as identification and use of pathogen-resistant germplasm (1, 7, 14,29). Studies of different citrus species and varieties have shown that sweet orange [Citrus sinensis (L.) Osbeck] and mandarin (C. reticulata Blanco) exhibit a wide range of resistance to ACC under various conditions and using different inoculation methods (7,11,14,29,30). Differences in varietal reaction among studies might be observed due to experimental conditions, local strains of Xcc or inoculation methods.…”
Section: Reaction Of Detached Leaves From Different Varieties Of Sweementioning
confidence: 99%
“…However, the citrus cultivars to be planted in Paraná need to have a certain level of resistance to citrus canker disease (Xanthomonas citri subsp. citri), which is one of the major concerns for citrus cultivation in the state (LEITE JUNIOR, 1992;VARGAS et al, 2013). Currently, the recommended sweet orange [Citrus sinensis (L.) Osbeck] cultivars for planting are 'Pêra', 'FolhaMurcha', 'Valencia', 'IAPAR-73', 'Natal', 'Navelina', 'Shamouti', 'Salustiana', 'Cadenera', and 'Jaffa' (PARANÁ, 2015;AULER et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the harvested area, this increase was related to the establishment of fruit processing industries aiming at the production of juice, especially in the northern and northwestern Paraná, the favorable soil and climate conditions for citrus production, the strong organization of citrus growers in cooperatives or associations, technical assistance, support for agricultural research and defense (AULER et al, 2014), prices reached by producers in the last harvests, and the growth potential of domestic and foreign markets (TAZIMA et al, 2008). Among the factors that have contributed to the improvement of orange production and productivity, the following stood out: more intensive use of inputs such as agricultural machines, implements, fertilizers, and pesticides; an improvement in the quality of genetic material, which enabled different species and varieties to adapt to the growing environment (MODA-CIRINO et al, 2012); management improvements (LEITE JUNIOR; MOHAN;1990;VARGAS et al, 2013), with emphasis on the densification of orchards, which is one of the practices for the control of diseases such as Huanglongbing (FUKUDA et al, 2010;MOREIRA et al, 2019). The harvested area and production increases were noted in advance by rural credit financing to finance production.…”
Section: Resultsmentioning
confidence: 99%